PUBLIC FINANCE AND ECONOMIC GROWTH IN WEST AFRICAN MONETARY ZONE COUNTRIES: A PANEL DATA ANALYSIS - Osho-Itsueli, Olubomi; Obi, Callistar K; Egbon , Peter C (Economics and Statistics Research Journal (ESRJ), 2024)
The relationship between economic growth and public finance in West African Monetary Zone Countries was examined in this study. The study used Gross Domestic Product per Capita as the dependent variable; and public expenditure, public revenue and public debt as the independent variables in the model specified. Using the Pooled Mean Group/ Autoregressive Distributed Lag technique to analyze panel data collected from the countries, the study revealed that public finance and economic growth have a positive relationship but the impact of public finance on economic growth was found to be non-significant. The study recommended sound fiscal governance and an efficient implementation of the National budget so that the operations of public finance would have a positive and significant effect on economic growth